Realidade aumentada distribuída na Web com independência de servidor para manipulação de objetos virtuais na camada cliente - Silva, Marlus Dias (2011)
This dissertation presents an architecture to the Argumented Reality environment distribution , using the Web as a mechanism of distribution and execution. Considering the works related with the referred topic, realizing the works use the web as a mechanism of distribution, and the environment is installed and configured in its works station. Facing this, there is the aim of a development in the distribution of the Argumented Reality environment which executes directly on the web, throughout the browser. To prove the architecture, it was created a software prototype. The Argumented Reality interface from this software is based on a case study which represents a specific area of knowledge, in this case, a continuous current motor. This way the Argumented Reality interface makes the interaction by the menu and marker. The architecture uses the model client/server , and it was divided in three layers in the server and four layers on the customers. The prototype was submitted by shocked tests and scalability to prove his performance with multiple users. The tests were conducted by 35 students from the high school (technological) and teachers from the information technology area. All of them used the system and answered a questionnaire based on the ISONORM. The results obtained permits to conclude the software is effective and applied.